Tailored antiplatelet therapy can overcome clopidogrel and aspirin resistance - The BOchum CLopidogrel and Aspirin Plan (BOCLA-Plan) to improve antiplatelet therapy - Neubauer, Horst (BioMed Central, 2011)
BACKGROUND: Dual antiplatelet therapy using acetylsalicylic acid (ASA, aspirin) and clopidogrel is of great importance following coronary stenting. However, the variable platelet inhibitory effectiveness compromises the antithrombotic advantages provided by dual antiplatelet therapy. The aim of this single-center prospective study was to reduce the low response incidence of dual antiplatelet therapy with ASA and clopidogrel according to a prespecified therapy algorithm. METHODS: Platelet function testing using whole blood aggregometry (Chronolog 590) was performed 48 hours following coronary stenting (for either acute coronary syndromes or stable coronary artery disease) on 504 patients. The antiplatelet therapy included a loading dose of 600 mg clopidogrel and 500 mg ASA, followed by 75 mg clopidogrel and 100 mg ASA once daily. Clopidogrel low responders (CLR: >5 ohm; adenosine diphosphate (ADP) 5 μM) and/or ASA low responders (ALR: >0 ohm; arachidonic acid 10 μM) were treated according to a structured therapy plan: in the case of CLR, the maintenance + dose was doubled (repeated loading dose followed by 150 mg daily), and when still ineffective ticlopidine or prasugrel, if available and not contraindicated, were used. ALR was treated by increasing the dose to 300 mg in a first step or to 500 mg ASA when the first modification did not take effect sufficiently. In addition, ADP receptor antagonist 2-methylthioadenosine 5'-monophosphate triethylammonium salt (MeSAMP) testing and ASA incubation were performed to rule out either a platelet ADP-receptor defect or an ASA pharmacokinetic resistance. RESULTS: Of the total cohort of 504 patients, we detected 30.8% clopidogrel low-responders and 19.4% aspirin low-responders. For ALR, with a dose adjustment of 300 mg ASA daily, 94.6% of ALR were effectively treated and the residual 5.4% by administration of daily dosages of 500 mg ASA. This means that after modification of the ASA maintenance dose, all initial ALRs had an adequate antiplatelet response. The results for clopidogrel revealed that 69% of the CLR were treated effectively by increasing the clopidogrel dose to 150 mg daily. When prasugrel was not available or contraindicated, 12.7% of the remaining low responders showed an adequate result after being switched to ticlopidine. Consequently, by applying the therapy algorithm, we were able to reduce the CLR prevalence by 86.6%. On including prasugrel in the therapy plan, we were finally able to eliminate thienopyridine low response. In addition, no ADP receptor defect was found in this study as a potential reason for CLR. We identified the following factors associated with both CLR and ALR status: acute coronary syndromes, positive troponin values as well as diabetes mellitus and elevated HbA(1C )values and a higher platelet count. Furthermore, our data revealed for CLR elevated C-reactive protein values and a high PREDICT-score (including an age >65 years, acute coronary syndrome, diabetes mellitus, renal failure, and reduced left ventricular function) as risk factors. The following factors correlated with the risk of ASA low response: patients with elevated hemoglobin, serum creatinine and C-reactive protein values. In addition, medication with nitrates reduced the risk of being CLR. As also holds true for CLR, we found the PREDICT-score to be correlated to the risk of being ALR. However, by far the strongest risk factor for CLR or ALR was the fact of dual resistance. CONCLUSION: Following a structured therapy plan based on a "test and treat" strategy, the prevalence of clopidogrel or aspirin low response can be significantly reduced and the risk of inadequate dual antiplatelet therapy minimized. TRIAL REGISTRATION: NCT01212302 (Clinicaltrials.gov)